Management of skin damage of health workers’ face: the role of plastic surgery in the time of Pandemic: Management of skin damages in Covid-19 pandemic - Cuomo, Roberto; Giardino, Francesco Ruben; Pozzi, Mirco; Nisi, Giuseppe; Sisti, Andrea; Han, Jingjian; Nuzzo, Angelo; Muratori, Alessia; Cigna, Emanuele; Losco, Luigi; Grimaldi, Luca (Acta Biomedica Atenei Parmensis, 2021)
Background The Sars-Cov-2 virus is characterized by a being highly contagiousness, and this is the reason why massive use of personal protective equipment is required by medical and paramedical staff of the COVID-19 dedicated departments. The aim of this manuscript is to describe and share our experience in the prevention and treatment of the personal protective equipment related pressure sores and other skin alterations in the medical and paramedical staff. Materials and methods All healthcare workers with PPE-related skin damages were registered at time 0. Age, sex, profession, type of skin damage, diseases and possible drugs were registered. Results Two strategies were emplyed: the first strategy was to immediately treat the skin and the second one was to prevent pressure wounds formation both in already affected healthcare workers and the recurrence in healed staff. Three weeks after the two strategies were used, the incidence rate PPE-related skin damage was reduced in a statistically significant way. Conclusions Proper management helps in reducing the incidence of pressure ulcers related to personal protective devices in CoVid-19 Units. Skin prevention and hydration, have been obtained achieved by using products applied at home, autonomously.